Stress and resilience in northern European marine ecosystems - Marcos Llope; Thorsten Blenckner; Paraskevas Vasilakopoulos; Niall McGinty; Christopher P. Lynam; Pierre Hélaouët; Christian Möllmann; Romain Frelat; Joël M. Durant; Leif C. Stige; Nils Chr. Stenseth (Proceedings of the National Academy of Sciences, 2026)
Marine ecosystems are facing multiple pressures from human activities, such as fishing and nutrient inputs from farming and agriculture, compounded by the global effects of climate change. As a result, the ecosystem services that societies depend on are at risk from the cumulative impact of these pressures. To better understand how different ecosystems respond, it is essential to assess their resilience. While predicting ecosystem resilience remains challenging, significant progress has been made in developing methods to measure it. In this study, we assessed resilience in four northern European marine ecosystems: the Icelandic Waters, the Barents Sea, the Baltic Sea, and the North Sea, spanning 3 to 5 decades. “Folded stability landscapes” were constructed for the Baltic and North Sea. This region provides a unique setting, with a south-north gradient from temperate to subarctic environments and a southeast-northwest gradient from open to semienclosed topographies. The Icelandic Waters and Barents Sea evolved relatively continuously, while the Baltic Sea and North Sea underwent more drastic changes. By comparing results across these gradients, we explore the role of isolation, level of pressures, and food web complexity in shaping resilience patterns and discuss the implications for managing resilient marine ecosystems in the future.